Influence of Coliform Source on Evaluation of Membrane Filters - Brodsky, M. H. (1975)
Four brands of membrane filters were examined for total and fecal coliform recovery performance by two experimental approaches. Using diluted EC broth cultures of water samples, Johns-Manville filters were superior to Sartorius filters for fecal coliform but equivalent for total coliform recovery. Using river water samples, Johns-Manville filters were superior to Sartorius filters for total coliform but equivalent for fecal coliform recovery. No differences were observed between Johns-Manville and Millipore or Millipore and Sartorius filters for total or fecal coliform recoveries using either approach, nor was any difference observed between Millipore and Gelman filters for fecal coliform recovery from river water samples. These results indicate that the source of the coliform bacteria has an important influence on the conclusions of membrane filter evaluation studies.